Development and utilization of engineered aquaponics recirculation system for aquacultures species - Azizah Endut (Terengganu: Universiti Malaysia Terengganu, 2012)
The integration of hydroponics plant production into recirculating aquaculture system namely aquaponics appears to be an excellent way of saving water, improve waste management as well as the production of a commercially useful hydroponics by products. The emergence of the self contained food production systems based on aquaponics is a fairly new concept and remains relatively undeveloped in Malaysia. This study was conducted to develop and utilize a pilot scale of aquaponics recirculation system (ARS) as the design protocol for the development of an economically feasible and environmentally sustainable aquaculture industry in Malaysia.